Review of Teacher Readiness in Implementing Merdeka Curriculum at Public Elementary Schools - Nabila Asti Sephiawardani; Kurniana Bektiningsih (Universitas Pendidikan Ganesha, 2023)
Education plays an important role in shaping the competence of the younger generation to face future challenges. The government implements the Merdeka Curriculum to improve the quality of Indonesian human resources globally. The aim of the Merdeka Curriculum is to expand the flexibility and adaptive capacity of teachers. There are obstacles in its implementation due to the limited resource capacity of public elementary schools. Some of the obstacles are teacher readiness, facilities, and curriculum evaluation. This research assesses the readiness of teachers to implement the Merdeka Curriculum at elementary school. Data collection was carried out using a purposive sampling technique through interviews with grade 1 and 4 teachers who understood the principles of the Merdeka Curriculum well. The results show that the learning process is coordinated and the teachers have prepared the design and learning media well. Supporting facilities such as teaching materials, learning videos, and school support smooth learning. However, an obstacle was found as an empirical finding that some teachers had difficulty adjusting students' skill levels considering the extent of the material and the implications of the pandemic. Several solutions to improve curriculum implementation include detailed material explanations, experience sharing, ongoing training, and regular evaluations.